Field efficacy of Porcilis® PCV M Hyo versus a licensed commercially available vaccine and placebo in the prevention of PRDC in pigs on a French farm: a randomized controlled trial. Issue 1 (December 2017) - Pagot, Eric; Rigaut, Martial; Roudaut, David; Panzavolta, Luca; Jolie, Rika; Duivon, Didier
Abstract Background A controlled, randomised, and blinded trial performed on a conventional French farrow-to-finish farm compared the efficacy of a one-shot bivalent ready to use vaccine, Porcilis® PCV M. Hyo (group PCVM), to that of two commercial vaccines (Ingelvac® Circoflex® + Ingelvac® Mhyo, group ICIM), and to a placebo (group CTL), in preventing the health and economic impacts of Porcine Respiratory Disease Complex (PRDC). Material & Methods In this small-scale clinical study, all piglets in each group were administered the vaccine/placebo at weaning age (27 days old). Piglets from either of the three groups were bled at regular intervals from 3 weeks of age until slaughter, in order to assess the infection by the main PRDC infectious agents:Mycoplasma hyopneumoniae, PCV2 and PRRSV. Performance, lung checks and slaughter data were collected and analysed. Results PCV2 viremia was significantly reduced in both vaccinated groups as compared to the placebo group. Lung lesion score was significantly lower in group PCVM, as compared to groups CTL and ICIM. Average daily weight gain during the finishing period was not significantly different between both vaccinated groups and was significantly higher than in the placebo group (849 g/d in the latter). Carcass results provided a numerical advantage to PCVM group, through improved part of production eligible for premium payment, and superior farmer income; this was a trend and did not reach significance. Conclusion The one-shot bivalent vaccine Porcilis® PCV M Hyo proved to be efficacious and convenient to use in a field context of active PCV2 andM. hyopneumoniae infections.